2015
DOI: 10.3141/2537-09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crime Statistics on Travel Mode Choice

Abstract: Whether crime or the perception of it has any direct and significant influence on travelers’ mode choice is a topic for which the evidence remains inconclusive. Studies have revealed various, and in some cases counterintuitive, roles that safety concerns can play in individuals’ travel behavior. In addition, characteristics of the physical environment such as land use and walkability are also influential factors in travelers’ decisions. This study explored these questions through the study of individual travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…For instance, Zhang reported that ridership responded negatively to a higher level of crime that exceeds a threshold of the ridership, although she agreed that higher population density is a factor that can stimulate crime near the bus access points ( 9 ). This study explained that crime and the fear of crime discourage travelers from taking public transit and has become an impediment for ridership growth, which is consistent with previous studies ( 19 ). Some other studies supported Jane Jacob’s hypothesis that there are more “eyes on the street” in crowded areas, leading to less crime opportunity ( 20 ).…”
Section: Literature Reviewsupporting
confidence: 92%
“…For instance, Zhang reported that ridership responded negatively to a higher level of crime that exceeds a threshold of the ridership, although she agreed that higher population density is a factor that can stimulate crime near the bus access points ( 9 ). This study explained that crime and the fear of crime discourage travelers from taking public transit and has become an impediment for ridership growth, which is consistent with previous studies ( 19 ). Some other studies supported Jane Jacob’s hypothesis that there are more “eyes on the street” in crowded areas, leading to less crime opportunity ( 20 ).…”
Section: Literature Reviewsupporting
confidence: 92%
“…Many empirical studies indicate the occurrence of incidents of sexual harassment in transit environments (e.g., Ball & Wesson, 2017;Gardner et al, 2017;Halat et al, 2015;Hoor-Ul-Ain, 2020;Horii & Burgess, 2012;S. Lewis et al, 2020;Madan & Nalla, 2015;Natarajan et al, 2017;Neupane & Chesney-Lind, 2014;Orozco-Fontalvo et al, 2019;Tripathi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This information is useful for the Chicago PD as it can concentrate additional resources on these two districts. Apparently, those two districts fall under Area Central covering Central, the Loop, and the Near North Side of Chicago and standing out as outliers exceeding all other districts' crime rates (Halat et al, 2015). The near North Side district has the highest number of skyscrapers, and the largest population with high per capita income.…”
Section: Locationmentioning
confidence: 93%